Xeno-Free Spheroids of Human Gingiva-Derived Progenitor Cells for Bone Tissue Engineering - Shanbhag, Siddharth; Suliman, Salwa; Bolstad, Anne Isine; Stavropoulos, Andreas; Mustafa, Kamal (Frontiers in Bioengineering and Biotechnology, 2020)
Gingiva has been identified as a minimally invasive source of multipotent progenitor cells (GPCs) for use in bone tissue engineering (BTE). To facilitate clinical translation, it is important to characterize GPCs in xeno-free cultures. Recent evidence indicates several advantages of three-dimensional (3D) spheroid cultures of mesenchymal stromal cells (MSCs) over conventional 2D monolayers. The present study aimed to characterize human GPCs in xeno-free 2D cultures, and to test their osteogenic potential in 3D cultures, in comparison to bone marrow MSCs (BMSCs). Primary GPCs and BMSCs were expanded in human platelet lysate (HPL) or fetal bovine serum (FBS) and characterized based on in vitro proliferation, immunophenotype and multi-lineage differentiation. Next, 3D spheroids of GPCs and BMSCs were formed via self-assembly and cultured in HPL. Expression of stemness- (SOX2, OCT4, NANOG) and osteogenesis-related markers (BMP2, RUNX2, OPN, OCN) was assessed at gene and protein levels in 3D and 2D cultures. The cytokine profile of 3D and 2D GPCs and BMSCs was assessed via a multiplex immunoassay. Monolayer GPCs in both HPL and FBS demonstrated a characteristic MSC-like immunophenotype and multi-lineage differentiation; osteogenic differentiation of GPCs was enhanced in HPL vs. FBS. CD271+ GPCs in HPL spontaneously acquired a neuronal phenotype and strongly expressed neuronal/glial markers. 3D spheroids of GPCs and BMSCs with high cell viability were formed in HPL media. Expression of stemness- and osteogenesis-related genes was significantly upregulated in 3D vs. 2D GPCs and BMSCs; the latter was independent of osteogenic induction. Synthesis of SOX2, BMP2 and OCN was confirmed via immunostaining, and in vitro mineralization via Alizarin red staining. Finally, secretion of several growth factors and chemokines was enhanced in GPC and BMSC spheroids, while that of pro-inflammatory cytokines was reduced, compared to monolayers. In summary, monolayer GPCs expanded in HPL demonstrate enhanced osteogenic differentiation potential, comparable to that of BMSCs. Xeno-free spheroid culture further enhances stemness- and osteogenesis-related gene expression, and cytokine secretion in GPCs, comparable to that of BMSCs.